The politics of violence in William Faulkner's Sanctuary - Abdullah, Omar Mohammed (Malaysian Association of Modern Languages, 2016)
Violence is an essential element in William Faulkner’s fictional world. Faulkner uses violence as an analytical perspective that connects his characters to their environment and it is categorized into many types; interpersonal, physical, sexual, racial…etc. The aim of the present paper is to chart the role of violence within the perspective of the gender identity and its politics in Faulkner’s novel Sanctuary. In this paper, the characters are the focus of violence and their being is targeted whether in a sexual way or any other means. Sanctuary in this paper is examined from the gender perspective, shedding light on the breaches that targeted the identity mainly represented in the protagonist Temple Drake. The paper explored the suffering of the society through the acts of rape, killing, dehumanization and the ramifications of these acts in this work.